PROJETO EM MULTINÍVEIS: UMA PROPOSTA DE PRÁTICA PEDAGÓGICA DIFERENCIADA EM UMA ESCOLA DA REDE MUNICIPAL DE ENSINO DE CASTELO/ES - Delesposte, Eliana Louzada (2022)
This paper aims to build collectively differentiated pedagogical practices, that provide quality education and that comply with the diversity of students in the context of the regular classroom, aiming to contribute to the school inclusion of these students in a class of early years of elementary school - from the municipality of Castelo/ES. It presents specific aims: carrying out a reading of the School's Political-Pedagogical Project; understanding the concepts of inclusion of professionals from the researched school, establishing dialogic relationships with the school's actors; analyzing the possibilities of building differentiated pedagogical practices showing through academic literature and practical experience The Project in Multi levels. Diagnosing the learning processes through evaluation and observation in the context of the common classroom of the students inserted in the class. Choosing as an educational product of the dissertation, a Multilevel Project that helps the teaching-learning process of all students, based on the demands presented by students in a common classroom class. The study took place in a school of the Municipal Network, located in the urban area of the Municipality of Castelo/ES. It was developed with a class of 5th grade of elementary school, with the participation of the head teacher, teacher of the Specialized Educational Assistance (AEE), tutoring teacher, caregiver and management team (principal and pedagogue). Of a qualitative way, it took on collaborative-critical action research as it is characterized as a collective methodology, allowing discussions, reflection on practice and the production of knowledge in a cooperative way. As data collection instruments, it used procedures such as document analysis, participant observation recorded in a field diary and the application of a questionnaire. To support the questions that emerged from the investigation process, it sought possible dialogues in the studies of Meirieu (2002, 2005), in addition to the theories of researchers in the area of Special Education. Data were produced from April to December 2021, organized and analyzed based on content analysis. The lived process, discussions and reflections showed that all students can have access to knowledge and success in learning if pedagogical practices are thought considering the learning path, based on the common curriculum, without ignoring the specificities and needs of students. In this way, it provides pleasant classes, with everyone involved in the same context, practicing activities of their interests and enabling the learning of all students, including students who are the target audience of Special Education. As an educational product of this research, the Multilevel Project is presented to support and guide the construction of other inclusive pedagogical practices that comply with the diversity of the classroom and favor education from an inclusive perspective. Keywords: Inclusive education; differentiated pedagogical practices; Multilevel Project.